Watak berperang bangsa Indonesia berbagai-bagai daerah : suatu perbandingan - Maaten, K. van der (Seri informasi Aceh ;, 1978)
Comparison between the war like character of the Achinese and other Indonesian ethnic groups toward the Dutch Colonial government.